Adopting a multi-systems approach: examining the academic belongingness of first-generation college students with multiple stigmatized identities in STEM - Google, Angela N.; Sekaya, Grace; McMullen, Zachery; Henning, Jeremiah A. (Frontiers in Education, 2023)
First-generation college students often experience greater social alienation and marginalization due to a mismatch of their cultural values compared to those of their university and often report lower academic satisfaction and sense of belonging. The effects on sense of belonging and satisfaction are intensified when first-generation college students have identities that intersect with other stigmatized social and cultural identities, like low socioeconomic status, Black or Latinx racial identities or religious identities, specifically for STEM majors. Students' holistic health and well-being, including their sense of belonging, is highly correlated to their academic achievement, persistence, and overall student success, especially for underrepresented minority groups. However, there has been limited consideration for the nuanced experiences of first-generation college students with multiple stigmatized identities, and for how the academic STEM environment shapes student's perceptions of inclusivity considering their social identities. To address these concerns, we used the Bioecological Systems theory to contextualize drivers of sense of belonging for students with stigmatized social and cultural identities by allowing space to explicitly consider institutional, departmental, classroom and societal-level phenomena that may operate to erode or fortify belonging for some individuals over others. Findings were organized contextually first, revealing how broader societal and familial values shaped their perceptions of their first-generation identity. Next, we reported how various forms of engagement and interactions with institutional agents impacted their perceptions of support at the institutional level. We then documented behavioral patterns within STEM departments that culminated to reveal how first-generation college students' sense of belonging was impacted by perceived departmental culture. Last, we revealed interactions within STEM classrooms that signaled inclusivity through humanizing and intentional pedagogical practices. Infused throughout all findings are instances where student experiences were mediated through their multiple identities and were shaped by dual global pandemics of 2020, that being COVID-19 and the racial unrest resurfaced by the murder of George Floyd. Implications for this work have the potential to restructure how institutions provide support for first-generation college students given the salience of their intersecting stigmatized identities in shaping their institutional, disciplinary, and classroom belonging.